2022
DOI: 10.1093/jas/skac139
|View full text |Cite
|
Sign up to set email alerts
|

Enteric methane emissions, growth, and carcass characteristics of feedlot steers fed a garlic- and citrus-based feed additive in diets with three different forage concentrations

Abstract: One hundred and forty-four Angus x Simmental steers were allotted by body weight (BW; 363 kg), breed composition, and farm origin to a 3 x 2 factorial arrangement of 6 treatments (4 pens per treatment) to determine the effect of Mootral (garlic + citrus extract; 0.25% of the diet DM vs. 0.0%) on methane emissions, growth and carcass characteristics of feedlot cattle. During the first 84 days, cattle were fed three different forage concentrations in the diet (15, 41.5, or 68% corn silage) with or without Mootra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…This emphasises the need to focus on enteric CH 4 mitigation strategies to achieve significant emission reductions and more sustainable dairy farming [ 55 ]. It is noteworthy that the current simulation did not include the potential enteric CH 4 -mitigating effect of GCE [ 11 , 12 , 13 , 14 ], which could further reduce the GHG emission intensity of milk. Indeed, it would be interesting for future LCA studies to evaluate how the combined effect of GCE in improving milk production and enteric CH 4 mitigation could influence the GHG emission intensity of dairy production.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This emphasises the need to focus on enteric CH 4 mitigation strategies to achieve significant emission reductions and more sustainable dairy farming [ 55 ]. It is noteworthy that the current simulation did not include the potential enteric CH 4 -mitigating effect of GCE [ 11 , 12 , 13 , 14 ], which could further reduce the GHG emission intensity of milk. Indeed, it would be interesting for future LCA studies to evaluate how the combined effect of GCE in improving milk production and enteric CH 4 mitigation could influence the GHG emission intensity of dairy production.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have demonstrated the enteric methane mitigation effect of feeding a garlic and citrus extract (GCE) supplement to dairy cows, sheep and beef cattle [ 11 , 12 , 13 , 14 ]. Supplementing GCE in a total mixed ration (TMR) has been shown to increase the milk yield and feed efficiency of dairy cows [ 11 ], potentially through positive modulation of rumen fermentation, which increases the production of volatile fatty acids (VFA) [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Feeding GAR to feedlot steers (15 g/steer/d) only showed a reduction in CH 4 after 9 wk of supplementation ( Roque et al., 2019 ). Another study on feedlot steers (0.25% of DMI) had no effect on CH 4 over an 84 d period at differing inclusion levels of forage (15%, 41.5%, and 68%); however, during the finishing period (15% forage inclusion), a 26% reduction in CH 4 g/d was observed ( Bitsie et al., 2022 ). It is therefore difficult to pinpoint the reasoning for the inconsistent effects of GAR on CH 4 production in ruminants, as the aforementioned studies were conducted over a variety of time periods (21 to 207 d) and as part of differing feeding regimes (15% and 68% forage).…”
Section: Discussionmentioning
confidence: 97%
“…Plant extracts are potential rumen modifiers because of their antimicrobial activity against microorganisms [ 49 ]. The wide application of plant extracts for reducing ruminal methane emissions supports their role as rumen modifiers [ 50 ]. Therefore, it is essential to evaluate the effects of RE on rumen functions.…”
Section: Discussionmentioning
confidence: 99%